Pharmacogenetic aspects of eprosartan therapy and polymorphic markers of renin-angiotensin-aldosterone system genes in Uzbek patients with essential arterial hypertension - D. R. Kurbanova; N. Z. Srozhidinova; N. B. Tursunova; M. R. Eliseeva (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To investigate antihypertensive and anti-remodeling effects of eprosartan in Uzbek patients with essential arterial hypertension (AH), taking into consideration renin-angiotensin-aldosterone system genetic polymorphism.Material and methods. The study included 48 Uzbek men with Stage I-II AH. Left ventricular (LV) myocardial mass was assessed by echocardiography (EchoCG), LV diastolic function — by Doppler EchoCG. Genomic DNA was extracted from peripheral blood leukocytes according to standard protocol, using the Diatom TM DNA Prep 200 kit. AGT, ACE, AT1R, and CYP11B2 gene polymorphism was investigated by gene amplification and primer PCR method. Eprosartan monotherapy lasted for 12 weeks.Results. Twelve-week eprosartan therapy was associated with a good antihypertensive effect, LV hypertrophy regression, and LV diastolic function improvement, regardless of ACE gene I/D polymorphism, AGT gene M235T polymorphism, AT1R gene A1166C polymorphism, or CYP11B2 gene C344T polymorphism.Conclusion. Antihypertensive effectiveness of eprosartan was independent of AGT, ACE, AT1R, or CYP11B2 gene polymorphic markers. LV hypertrophy regression during eprosartan treatment was associated with DD genotype of ACE gene I/D polymorphism, TT genotype of AGT gene М235Т polymorphism, AA genotype of AT1R gene А1166С polymorphism, and CT genotype of CYP11B2 gene С344Т polymorphism.